PEMANFAATAN INFORMATION AND COMMUNICATION TECHNOLOGIES (ICT) DALAM BIDANG E-COMMERCE DI DUSUN SEMAWUNG SEDAYU MUNTILAN - Renna Yanwastika Ariyana (LPPM IST AKPRIND Yogyakarta, 2019)
The growing development of transactions electronically or often referred to as E-Commerce makes people have to be able to innovate to open alternative business online by utilizing existing ICT advancements. The use of ICT in marketing products or services that are owned can take advantage of marketplace and social media available for free on the Internet. This is so that the transaction process is much easier and has a wider marketing reach. Community service carried out in Semawung Hamlet, Sedayu Village, Muntilan Subdistrict, Magelang Regency aims to provide information on the use of ICT in the field of E-Commerce. From the results of interviews with the residents of Semawung Hamlet, the residents still feel confused and have difficulty in marketing the agricultural products they get, because agricultural products are only sold to collectors at very cheap prices. Therefore, community members need a socialization of how to market the agricultural products that they get with a much wider range of regions by utilizing the advancement of ICT.